Optimization of sepsis therapy based on patient-specific digital precision diagnostics using next generation sequencing (DigiSep-Trial): study protocol for a randomized, controlled, interventional, open-label, multicenter trial - Brenner, Thorsten; Skarabis, Annabell; Stevens, Philip; Axnick, Jennifer; Haug, Peter; Grumaz, Silke; Bruckner, Thomas; Luntz, Steffen P.; Witzke, Oliver; Pletz, Mathias W.; Ruprecht, Thomas M.; Marschall, Ursula; et al. (Trials, 2021)
Sepsis is triggered by an infection and represents one of the greatest challenges of modern intensive care medicine. With regard to a targeted antimicrobial treatment strategy, the earliest possible pathogen detection is of crucial importance. Until now, culture-based detection methods represent the diagnostic gold standard, although they are characterized by numerous limitations. Culture-independent molecular diagnostic procedures represent a promising alternative. In particular, the plasmatic detection of circulating, cell-free DNA by next-generation sequencing (NGS) has shown to be suitable for identifying disease-causing pathogens in patients with bloodstream infections.
Gesehen am 30.12.2021